Pengaruh, Transparansi, Akuntabilitas, Dan Partisipasi Masyarakat Terhadap Pengelolaan Alokasi Dana Desa (Studi Kasus Pada Desa Di Kecamatan Nganjuk, Kabupaten Nganjuk) - Marhaendra Ihza Pahlevi; Endah Susilowati; Astrini Aning Widoretno (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study is to test and prove transparency, accountability, and community participation in the management of village fund allocations in villages in Nganjuk sub-district, Nganjuk district. The type of research used is quantitative research. The research population is village officials, BPD, and community representatives in villages in Nganjuk District, Nganjuk Regency. Sampling technique using random sampling or random sampling. The results showed that transparency, accountability, and community participation contributed to the management of village fund allocations in villages in Nganjuk sub-district, Nganjuk district. Thus, village officials in villages in Nganjuk District, are able to implement and improve the management of village fund allocations that are accountable, transparent, and participatory in accordance with applicable regulations so that they become more advanced villages and better financial management. Keywords: Transparency, Accountability, Society participation